High school sport specialization patterns of current Division I athletes - Post, E. G.; Thein-Nissenbaum, J. M.; Stiffler, M. R.; Brooks, M. A.; Bell, D. R.; Sanfilippo, J. L.; Trigsted, S. M.; Heiderscheit, B. C.; McGuine, T. A. (Sports Health: A Multidisciplinary Approach, 2017)
Sport specialization is a strategy to acquire superior sport performance in 1 sport but is associated with increased injury risk. Currently, the degree of high school specialization among Division I athletes is unknown. Hypothesis: College athletes will display increased rates of specialization as they progress through their high school careers. Study Design: Descriptive epidemiological study. Level of Evidence: Level 4. Methods: Three hundred forty-three athletes (115 female) representing 9 sports from a Midwest Division I University completed a previously utilized sport specialization questionnaire regarding sport participation patterns for each grade of high school. McNemar and chi-square tests were used to investigate associations of grade, sport, and sex with prevalence of sport specialization category (low, moderate, high) (a priori P = 0.05). Results: Specialization increased throughout high school, with 16.9% (n = 58) and 41.1% (n = 141) of athletes highly specialized in 9th and 12th grades, respectively. Football athletes were less likely to be highly specialized than nonfootball athletes for each year of high school (P < 0.001). There was no difference in degree of specialization between sexes at any grade level (P > 0.23). Conclusion: The majority of Division I athletes were not classified as highly specialized throughout high school, but the prevalence of high specialization increased as athletes progressed through high school. Nonfootball athletes were more likely to be highly specialized than football athletes at each grade level. Clinical Relevance: Most athletes who are recruited to participate in collegiate athletics will eventually specialize in their sport, but it does not appear that early specialization is necessary to become a Division I athlete. Athletes should be counseled regarding safe participation in sport during high school to minimize injury and maximize performance.